2007
DOI: 10.1300/j125v15n04_03
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration for the Provision of Services

Abstract: This paper conducts a review of the extant literature to examine community collaboration in the provision of human services. The authors conducted a systematic research synthesis to organize literature around how community organizations should position themselves in order to maximize the benefits of collaborative relationships while enhancing service provision. Evaluation of the literature reveals 30% of the articles could be classified as empirical. Due to limitations of the studies no definitive statements c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 70 publications
(96 reference statements)
2
21
0
Order By: Relevance
“…The interviews also revealed a number of factors that hinder collaborative practice, along with strategies for mediating problems associated with these factors. The findings from this study affirm the importance of many elements of successful collaboration that are reflected in social work literature: strong leadership; shared vision; structures and processes to facilitate the creation and evolution of collaborative efforts; role clarity; defined goals; attention to member composition, relationship building, and team building; and achievement of interim successes (Bertram, 2008;Dunlop & Holosko, 2004;Ferguson, 2004;Fitch, 2009;Harbert, 1997;Jones, Crook, & Webb, 2007;Reilly, 2001;Slaght & Hamilton, 2005;Spath, Werrbach, & Pine, 2008;Urwin, 1998). The importance of trust, communication, shared vision, and adoption of values consistent with collaboration among stakeholders and facilitators is also reflected in the literature (Bayne- Smith, Mizrahi, & Garcia, 2008;Jones et al, 2007;Potito, Day, Carson, & O'Leary, 2009).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The interviews also revealed a number of factors that hinder collaborative practice, along with strategies for mediating problems associated with these factors. The findings from this study affirm the importance of many elements of successful collaboration that are reflected in social work literature: strong leadership; shared vision; structures and processes to facilitate the creation and evolution of collaborative efforts; role clarity; defined goals; attention to member composition, relationship building, and team building; and achievement of interim successes (Bertram, 2008;Dunlop & Holosko, 2004;Ferguson, 2004;Fitch, 2009;Harbert, 1997;Jones, Crook, & Webb, 2007;Reilly, 2001;Slaght & Hamilton, 2005;Spath, Werrbach, & Pine, 2008;Urwin, 1998). The importance of trust, communication, shared vision, and adoption of values consistent with collaboration among stakeholders and facilitators is also reflected in the literature (Bayne- Smith, Mizrahi, & Garcia, 2008;Jones et al, 2007;Potito, Day, Carson, & O'Leary, 2009).…”
Section: Discussionsupporting
confidence: 71%
“…The findings from this study affirm the importance of many elements of successful collaboration that are reflected in social work literature: strong leadership; shared vision; structures and processes to facilitate the creation and evolution of collaborative efforts; role clarity; defined goals; attention to member composition, relationship building, and team building; and achievement of interim successes (Bertram, 2008;Dunlop & Holosko, 2004;Ferguson, 2004;Fitch, 2009;Harbert, 1997;Jones, Crook, & Webb, 2007;Reilly, 2001;Slaght & Hamilton, 2005;Spath, Werrbach, & Pine, 2008;Urwin, 1998). The importance of trust, communication, shared vision, and adoption of values consistent with collaboration among stakeholders and facilitators is also reflected in the literature (Bayne- Smith, Mizrahi, & Garcia, 2008;Jones et al, 2007;Potito, Day, Carson, & O'Leary, 2009). Findings from this study are also consistent with other studies that found multiple factors that impede collaboration, such as conflicts in perspectives and priorities, staff turnover, barriers to sharing confidential information, and changes in systems and resources (Altshuler, 2003;Darlington, Feeney, & Rixon, 2005;Han, Carnochan, & Austin, 2007;Ryan, Tracy, Rebeck, Biegel, & Johnsen, 2001;Spath et al, 2008).…”
Section: Discussionsupporting
confidence: 71%
“…After an extensive review of the literature on collaboration, Jones, Crook, and Webb (2007) suggested that More research is needed on the training that is necessary for staff and members of organizations to obtain the skills for effective participation in the collaborative process (i.e., how do organizations best prepare their human capital for participation in the collaborative process?). Another need in the literature involves the use of different management models and practices (i.e., top-down, democratic, quality circles, etc.)…”
Section: Implications For Researchmentioning
confidence: 99%
“…This has been sparked by the increase in budget shortfalls and multi-problem clients, who often receive services from workers in different organizations (e.g., child protection, income maintenance, and behavioral health). One approach to these concerns has been to achieve more coherent and effective human service systems through services integration and coordination (Austin, 1997;Jones, Crook, & Webb, 2007). Goals have included finding ways to reduce fragmentation and service gaps to improve access and continuity of care, minimize duplication and redundancy in order to lower costs (e.g., time and inconvenience) for clients, utilize scarce resources more effectively, and achieve greater accountability.…”
Section: Introductionmentioning
confidence: 99%
“…Head, 2008;Spath, Werrbach, & Pine, 2008); the development of shared understandings and goals (Horwath & T.Morrison, 2007); strong and competent leadership (Jones et al, 2008); and adequate resource allocation (Metcalfe, Riedlinger, McKenzie, & Cook, 2007). Within the context of statutory child protection, these factors may be challenging to implement in practice.…”
Section: Benefits and Challenges Of Collaborative Practicementioning
confidence: 99%